Preclinical Performance of a Novel Dental Implant Design Reducing Mechanical Stress in Cortical Bone - Carolin Erbel; Matthias W. Laschke; Tanja Grobecker-Karl; Matthias Karl (Journal of Functional Biomaterials)
This animal study compared the healing performance of a novel implant design characterized by a shift in thread geometry and core diameter with two different surfaces with that of an apically tapered implant. Test Bioactive (n = 9), Test Porous (n = 7) and Control (n = 8) implants were placed in the mandibles of minipigs. Following healing, bone samples were harvested for determining bone-to-implant contact (BIC) and marginal bone loss (MBL). Comparative statistics were based on Levene’s test, Shapiro–Wilk tests, the Kruskal–Wallis test and Wilcoxon tests with Holm correction (α = 0.05). The mean undersizing of the osteotomy was 0.15 mm for Control, while in the test groups 0.33 mm and 0.34 mm were calculated. Insertion torques ranged from 61.5 Ncm (Control) to 76.1 Ncm (Test Bioactive). Maximum BIC was seen in Test Porous with 55.83%, while Test Bioactive showed only 48.11%. MBL was 4.1 mm in Test Bioactive, while Test Porous and Control exhibited 2.8 mm. No significant differences between the implant groups were observed (p > 0.05). Despite greater undersizing, the novel implant type performed comparably to the established Control implants. The rougher surface of the bioactive implants increased the insertion torque and led to more MBL.